Antidepressant effect of electroacupuncture regulates signal targeting in the brain and increases brain-derived neurotrophic factor levels - Dong-mei Duan; Ya Tu; Ping Liu; Shuang Jiao (Neural Regeneration Research, 2016)
Electroacupuncture improves depressive behavior faster and with fewer adverse effects than antidepressant medication. However, the antidepressant mechanism of electroacupuncture remains poorly understood. Here, we established a rat model of chronic unpredicted mild stress, and then treated these rats with electroacupuncture at Yintang (EX-HN3) and Baihui (DU20) with sparse waves at 2 Hz and 0.6 mA for 30 minutes, once a day. We found increased horizontal and vertical activity, and decreased immobility time, at 2 and 4 weeks after treatment. Moreover, levels of neurotransmitters (5-hydroxytryptamine, glutamate, and γ-aminobutyric acid) and protein levels of brain-derived neurotrophic factor and brain-derived neurotrophic factor-related proteins (TrkB, protein kinase A, and phosphorylation of cyclic adenosine monophosphate response element binding protein) were increased in the hippocampus. Similarly, protein kinase A and TrkB mRNA levels were increased, and calcium-calmodulin-dependent protein kinase II levels decreased. These findings suggest that electroacupuncture increases phosphorylation of cyclic adenosine monophosphate response element binding protein and brain-derived neurotrophic factor levels by regulating multiple targets in the cyclic adenosine monophosphate response element binding protein signaling pathway, thereby promoting nerve regeneration, and exerting an antidepressive effect.